2004
DOI: 10.1038/ng1333
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of population stratification on genetic association studies

Abstract: Population stratification refers to differences in allele frequencies between cases and controls due to systematic differences in ancestry rather than association of genes with disease. It has been proposed that false positive associations due to stratification can be controlled by genotyping a few dozen unlinked genetic markers. To assess stratification empirically, we analyzed data from 11 case-control and casecohort association studies. We did not detect statistically significant evidence for stratification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
544
3
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 738 publications
(554 citation statements)
references
References 24 publications
4
544
3
3
Order By: Relevance
“…Even prior to the formal test, we felt that we were at low risk for stratification artifact because extraversion, the phenotype with the strongest and most consistent findings in this study, was not observed to be significantly different among Hispanics and EAs (the two groups large enough to permit comparison), although such differences did appear for neuroticism. However, without a formal test for stratification, it could also have been argued that in the worst case, this could have led to a false positive finding via population stratification (Freedman et al, 2004). However, using a set of 36 markers including 21 that were selected specifically for their population-distinguishing characteristics, we tested formally for possible effects of population structure in creating spurious association, and were able to exclude this possibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even prior to the formal test, we felt that we were at low risk for stratification artifact because extraversion, the phenotype with the strongest and most consistent findings in this study, was not observed to be significantly different among Hispanics and EAs (the two groups large enough to permit comparison), although such differences did appear for neuroticism. However, without a formal test for stratification, it could also have been argued that in the worst case, this could have led to a false positive finding via population stratification (Freedman et al, 2004). However, using a set of 36 markers including 21 that were selected specifically for their population-distinguishing characteristics, we tested formally for possible effects of population structure in creating spurious association, and were able to exclude this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…Population subdivision is thought to be a major potential confound for case-control association studies (Freedman et al, 2004). We therefore used the method of Pritchard and Rosenberg (1999) to evaluate the potential for spurious association in our study sample that would result from population stratification (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…A subset of subjects (N ¼ 150) was identified, consisting of all those who described themselves as being of European-American (Caucasian) ancestry; initial analyses were conducted on this subset in order to reduce the possibility of confounding by population stratification (Freedman et al, 2004).…”
Section: Sample and Proceduresmentioning
confidence: 99%
“…[1][2][3][4] Especially, as only a small number of SNPs are genotyped in candidate gene association studies (CGAS), which do not provide sufficient ancestry information, an independent set of ancestry informative markers (AIMs) is necessary to detect and control potential population stratification. To discern the ancestry of Europeans or European Americans, multiple sets of AIMs have been established that allow correction for population stratification in association studies using Europeans.…”
Section: Introductionmentioning
confidence: 99%